Contemporary grandparenting : changing family relationships in global contexts - Arber, Sara, 1949-; Timonen, Virpi (Policy, 2012)
This is the first book to take a sociological approach to grandparenting across diverse country contexts and combines new theorising with up-to-date empirical findings to document the changing nature of grandparenting across global contexts.